Primary sources, pedagogy and the politics of tertiary history in Australia. Issue 2 (3rd April 2022) - Neal, Kathleen B.; Ferns, Nicholas
Abstract: History education in Australian universities finds itself under increasing pressure in the age of neoliberalism and the crisis precipitated by COVID-19. Universities and professional associations have been forced to adopt a generic discourse of transferable 'skills' in order to justify the place of history in the curriculum. We show, however, that these skills may have specific or even contested meanings within disciplines. Moreover, students can only properly acquire higher-order transferable skills by practising them in disciplinary contexts. Consequently, reinvesting skills with disciplinary meaning is necessary for student outcomes even within a neoliberal rationale, enabling a new defence of the specific nature of historical work. We advance a means of working with primary sources using strategic questioning of increasing complexity as a tool for achieving these twin goals. We show how our approach is embedded in the cognitive processes of historical thinking as defined in both of the major theoretical models that have achieved currency, and posit it as a mode of pedagogical resistance in the neoliberal university landscape.